Praktyczne odzwierciedlenie wiedzy o kosztach jakości: The practical use of quality costs - Kwintowski, Andrzej (Management and Administration Journal, 2021)
Quality costs is an important factor for Polish managers when making sound economic decisions. High operating costs reduce the competitiveness of domestic and international business. Therefore a successful business needs to optimize its total cost by monitoring profit and cost balances. I will present in this article the practical use of quality costs in accordance with the ISO 9000 Norm.